Increased Expression of FGF19 Contributes to Tumor Progression and Cell Motility of Human Thyroid Cancer. (January 2016) - Zhang, Xiliang; Wang, Zhonghua; Tian, Lei; Xie, Jiangping; Zou, Guijun; Jiang, Futing
Objective: Numerous reports indicate a role for aberrant expression of fibroblast growth factor 19 (FGF19) in tumor development and progression, and several drugs have been developed to target it. The aim of this study was to investigate the clinical significance of FGF19 and examine whether it plays any roles in progression of thyroid cancer. Study Design: Translation research. Setting: Navy General Hospital of Chinese PLA, China. Subjects and Methods: Expression patterns of FGF19 protein in 100 paired formalin-fixed and paraffin-embedded cancerous and adjacent noncancerous tissues from patients with thyroid cancer were detected by immunohistochemistry. Then, in vitro migration and invasion assays of siRNA-targeted FGF19-transfected cells were performed. Results: Positive immunostaining of FGF19 protein expression was localized in cytoplasm with or without membrane of malignant cells and was observed in 82 (82.0%) of 100 patients with thyroid cancer. Statistically, the expression level of FGF19 protein in thyroid cancer tissues was significantly higher than that in normal tissues. In addition, FGF19 overexpression was significantly associated with the advanced tumor node metastasis staging ( P = .008), the presence of extrathyroidal invasion ( P = .01), lymph nodes metastasis ( P = .01), and distant metastasis ( P = .02). Furthermore, knockdown of FGF19 by transfection of siRNA-FGF19 could efficiently suppress the migration and invasion abilities of thyroid cancer cells in vitro. Conclusion: Our data revealed that the increased expression of FGF19 might be involved in the malignant behaviors of thyroid cancer, highlighting its potential as a molecular marker for early diagnosis and as a possible target for therapeutic intervention of this disease.